2011
DOI: 10.1007/s10745-011-9427-6
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Ecological Knowledge of Swiss Alpine Farmers and their Resilience to Socioecological Change

Abstract: The cultural landscape of the European Alps was formed over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 20 publications
1
41
0
2
Order By: Relevance
“…My study demonstrated that even in participatory restoration programs, where the public voluntarily collaborate with professional practitioners on a more equal footing, such power dynamics still exist. Second, although political ecologists have interrogated knowledge politics involved in environmental issues, their analyses focused on starkly different knowledge systems, for example, Western science versus resource users in developing countries (Forsyth, 2003;Robbins, 2003;Goodman, 2011) and traditional ecological knowledge (Nadasdy, 1999;Fernandez-Gimenez et al, 2006;von Glasenapp and Thornton, 2011). My study demonstrated that even in the first-world, urban context, among groups supportive of restoration, knowledge politics still lead to tensions.…”
Section: Refocusing On the Politics Of Participation And The Role Of mentioning
confidence: 90%
“…My study demonstrated that even in participatory restoration programs, where the public voluntarily collaborate with professional practitioners on a more equal footing, such power dynamics still exist. Second, although political ecologists have interrogated knowledge politics involved in environmental issues, their analyses focused on starkly different knowledge systems, for example, Western science versus resource users in developing countries (Forsyth, 2003;Robbins, 2003;Goodman, 2011) and traditional ecological knowledge (Nadasdy, 1999;Fernandez-Gimenez et al, 2006;von Glasenapp and Thornton, 2011). My study demonstrated that even in the first-world, urban context, among groups supportive of restoration, knowledge politics still lead to tensions.…”
Section: Refocusing On the Politics Of Participation And The Role Of mentioning
confidence: 90%
“…Furthermore, the implementation of crop-tree-livestock systems was significantly and positively correlated with farmers' knowledge of agrobiodiversity (crops, trees and animal species) management. These results highlighted the critical role of farmers' ecological knowledge in managing natural resources and local environment [51,58] and in enhancing the social-ecological resilience to hazards [59,60].…”
Section: Linking the Current With The Future Farming Contexts: Implicmentioning
confidence: 91%
“…This type of knowledge can not only be integrated to modern practices, but may also remain intact through years, persisting through changes and evolving rather than changing or being altered (Reyes-García et al, 2014). Tacit knowledge has also been reported as an element of the adaptive capacity of an agricultural production system (von Glasenapp and Thornton, 2011). Despite the fact that these knowledge endowments are important for livestock farms, migrant workers are not always experienced in such settings and need proper training (usually informal) during the first period of their employment.…”
Section: Particularities Of Labor In Livestock Farmsmentioning
confidence: 99%